2019
DOI: 10.2196/13748
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Using a 3D Visual Metaphor Serious Game to Teach History-Taking Content to Medical Students: Longitudinal Mixed Methods Pilot Study

Abstract: BackgroundHistory taking is a key component of clinical practice; however, this skill is often poorly performed by students and doctors.ObjectiveThe study aimed to determine whether Metaphoria, a 3D serious game (SG), is superior to another electronic medium (PDF text file) in learning the history-taking content of a single organ system (cardiac).MethodsIn 2015, a longitudinal mixed methods (quantitative and qualitative) pilot study was conducted over multiple sampling time points (10 weeks) on a group of unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 112 publications
(128 reference statements)
3
16
0
Order By: Relevance
“…The study reinforces the use of games as a learning method but also demonstrates the need for more research into the pp 25-43 • Clinical Simulation in Nursing • Volume 66 usability of games. Similar results have been reported by Alyami et al (2019) and Qi et al (2020) . However, the 3D simulation game is a more attractive, and motivating learning method ( Chang et al, 2021 ;Verkuyl et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…The study reinforces the use of games as a learning method but also demonstrates the need for more research into the pp 25-43 • Clinical Simulation in Nursing • Volume 66 usability of games. Similar results have been reported by Alyami et al (2019) and Qi et al (2020) . However, the 3D simulation game is a more attractive, and motivating learning method ( Chang et al, 2021 ;Verkuyl et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, regarding the students' attitude towards 3D printing, gender, age, and educational level were found to be significantly important. According the international literature, other researchers have shown that medical students or physicians have developed a positive perception of the new education methodology [3,4] and show that there is great interest in the latest advances in 3D printing technology in clinical practice [5,6]. The increasing use of the internet for scientific purposes has been associated with more knowledge about the applications and uses of 3D printers.…”
Section: Resultsmentioning
confidence: 99%
“…To better present the results, we created Table 2 that details the purposes of each visual communication related category and lists all the studies. (Alcivar et al, 2021), (Tuah et al, 2021, (Zhang et al, 2021), (Sarić et al, 2021), (Plass et al, 2020), (Pagano et al, 2020), (Gee and Dolah, 2020), (Alyami et al, 2019), (Gee and Dolah, 2018a), (Gee and Dolah, 2018b) (Javora et al, 2018), (Ontañón et al, 2017), (Gee and Dolah, 2016), (Selmbacherova et al, 2014), (Veinott et al, 2014), (Wang and Lee, 2014) , (Wattanasoontorn et al, 2013), (Bedi et al, 2011) , (Kartiko et al, 2010)…”
Section: Resultsmentioning
confidence: 99%